Childhood bullous pemphigoid successfully treated with topical corticosteroid. - Can Kuru, Burçe; Özkanlı, Şeyma; Zindanci, İlkin and Serap Karadağ, Ayşe and Gökçedağ, Gizem (European Journal of Pediatric Dermatology, 2020)
Bullous pemphigoid (BP) is an acquired, autoimmune subepidermal bullous skin disease commonly seen among older adults. However, it can rarely be seen among infants and children as well (1). Even though exact prevelance of BP in infants is unknown, it is reported to be the second most common autoimmune bullous disease among children after linear IgA disease. Lesions in children are more extensive and mainly acrolocated (2); palmoplantar lesions are the main diagnostic clue (3). Mucous membranes are rarely affected (2). The possible causes of infantile BP are foreign antigens as infectious agents, medicines, vaccines etc. (2, 3). Pediatric BP and BP in older adults are histologically identical; however, pediatric BP has a better prognosis (4). Linear IgG and C3 staining along the basement membrane zone in direct immunofluorescence test is the gold standart for diagnosis (3). Chronic bullous disease of childhood, dermatitis herpetiformis, bullous lupus eritematosus, epidermolysis bullosa acquisita, porfiria and bullous impetigo should be considered in the differential diagnosis (3). As the main treatment choice topical corticosteroids should be used for localized lesions, and systemic corticosteroids (prednisone 1-2 mg/kg/day) for more extensive lesions (3). For more stubborn lesions dapsone, IVIG, mycophenolate mofetil, eritromycine, methotrexate, cyclophosphamide, azathioprine, rituximab or omalizumab can also be considered as alternative treatment options (3). Our patient in spite of extensive lesions responded to topical treatment with mometasone furoate.